Efectos de la técnica watsu en la parálisis cerebral infantil - Dután Arízaga, Ana Patricia (2019)
This research work is framed in the Effects of the Watsu technique in childhood cerebral palsy. The need to analyze the effects and benefits of the Watsu technique was successful by reviewing different bibliographic sources so that it can be applied in children with cerebral palsy. The present investigation was based on the investigation of several articles with great scientific contribution that make reference to the application of the Watsu technique in infantile cerebral palsy, the methodology applied is qualitative since the information obtained about the Watsu technique in infantile cerebral palsy It was taken from different digital databases. 35 articles with great scientific contribution were taken in which they refer to patients with infantile cerebral palsy from databases such as PubMed, Elsevier, Scielo, Google scholar, Proquest, which are validated by the PEDro scale. The different authors agree that when applying the Watsu technique you will have noticeable results, because an important reduction in stiffness and tension of the body is obtained, increasing mobility, flexibility, muscle relaxation and deep breathing, therefore, the Watsu technique is of paramount importance in childhood cerebral palsy.